Study on Surface-Enhanced Raman Scattering Substrate Based on Titanium Oxide Nanorods Coated with Gold Nanoparticles - Xiaodong Wang; Xiulan Cheng; Xufeng Yu; Xueling Quan (Journal of Nanotechnology)
A 3D surface-enhanced Raman scattering (SERS) substrate based on titanium oxide nanorods (TiOx-NRs) coated with gold nanoparticles (Au-NPs) was fabricated by a simple hydrothermal, no-template process. The nanostructure of TiOx-NRs influenced by the concentrations of hydrochloric (HCl) acid and sodium chloride (NaCl) was studied in detail. The substrate showed the strongest Raman enhancement, when the diameters of Au-NPs were around 40 nm and the gaps of Au-NPs were in the range of 5 nm to 10 nm. The surface electric field of our substrate was examined by finite-different time-domain (FDTD) solutions. Rhodamine 6G (R6G) was chosen as the probe molecule to study the SERS performance of the substrates. The Raman signal of 10−10 M R6G was detected clearly by the substrate with the enhancement factor of 2.64 × 108. All relative standard deviation (RSD) values of the major peaks for R6G were within the scope of 10.4% to 16.7%. The substrate could work efficiently even after immersed in water for one month.